2009
DOI: 10.1103/physrevd.80.023506
|View full text |Cite
|
Sign up to set email alerts
|

Bounds on cross sections and lifetimes for dark matter annihilation and decay into charged leptons from gamma-ray observations of dwarf galaxies

Abstract: We provide conservative bounds on the dark matter cross-section and lifetime from final state radiation produced by annihilation or decay into charged leptons, either directly or via an intermediate particle φ. Our analysis utilizes the experimental gamma-ray flux upper limits from four Milky Way dwarf satellites: HESS observations of Sagittarius and VERITAS observations of Draco, Ursa Minor, and Willman 1. Using 90% confidence level lower limits on the integrals over the dark matter distributions, we find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
142
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 107 publications
3
142
0
Order By: Relevance
“…A point is shown for each model, orange points corresponding to pMSSM models for which Ωh 2 | LSP ≥ 0.1. The red line represents the estimated sensitivity for the LAT to detect a point source signal at high galactic latitudes with 3σ confidence [103].…”
Section: Jhep01(2011)064mentioning
confidence: 99%
See 3 more Smart Citations
“…A point is shown for each model, orange points corresponding to pMSSM models for which Ωh 2 | LSP ≥ 0.1. The red line represents the estimated sensitivity for the LAT to detect a point source signal at high galactic latitudes with 3σ confidence [103].…”
Section: Jhep01(2011)064mentioning
confidence: 99%
“…12 Although, as emphasized in [46,103], stellar kinematic data fix the normalization of ρ and ρ 2 such that the detailed nature of the inner-slope of the halo ends up having a relatively small effect on the total halo integral. 13 A rough calculation of these contributions (without any attempt to include the LAT instrument response) showed that the line contribution to the total yield of gammas would be > 1% in only ≈ 0.5% of the models in our pMSSM set.…”
Section: Jhep01(2011)064mentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly after the proposal of using DM annihilation to account for the data, the γ-ray and radio emissions from the Galactic center [13][14][15], the Milky Way halo [16][17][18][19][20], the dwarf galaxies [21][22][23], the galaxy clusters [24,25] and the early Universe [26][27][28] were studied as possible constraints and/or future probes of the DM models. These studies have shown that the proposed DM scenarios are either excluded or at least strongly constrained if the DM halo properties derived from current numerical simulations are adopted.…”
Section: Introductionmentioning
confidence: 99%